ﺔﻴﺑﺮﻌﻟﺍ ﺔﻐﻠﻟﺍ : ﺔﺜﻳﺪﳊﺍ ﺎﻴﺴﻴﻧﻭﺪﻧﺇ ﰲ ﺎﻬﻤﻠﻌﺗﻭ ﺎﻬﻤﻴﻠﻌﺗ (ﺔﻴﺟﺫﻮﳕ ﺔﻴﻌﻗﺍﻭ ﺓﺀﺍﺮﻗ) - Dihyatun Masqon (Universitas Darussalam Gontor, 2012)
This article describes various tricks in learning and teaching Arabic language. There are four important aspects: listening, speaking, reading and writing. These four aspects are integral language activities which are practiced simultaneously . Moreover, it is said that there is nothing can be spoken before listening, there is nothing can be read before speaking, and there is nothing can be written before reading. Meanwhile, in practice, a language learner should start with a lot of practical exercises and not use translation method. These exercises can be in the form of structuring, repeating, and communicating. However, the aspect of teacher takes very important point. Without a good teacher, a good subject, system, and method are useless. Method is more important than subject, teacher is more important than method, and the soul of the teacher is the most important. Beside those, creating a milieu conducive to language learning is sine qua non and fundamental element for the improvement of Arabic language.